Comparative Study between the Diagnostic Effectiveness of Brain SPECT with [123I]Ioflupane and [123I]MIBG Scintigraphy in Multiple System Atrophy - Javier Villena-Salinas; Simeón José Ortega-Lozano; Tomader Amrani-Raissouni; Eduardo Agüera-Morales; Javier Caballero-Villarraso (Biomedicines, 2024)
Background: Multiple system atrophy (MSA) is a neurodegenerative disease. It has a fast progression, so early diagnosis is decisive. Two functional imaging tests can be involved in its diagnosis: [123I]Ioflupane SPECT and [123I]MIBG scintigraphy. Our aim is to comparatively analyze the diagnostic performance of both techniques. Methods: 46 patients (24 males and 22 females) with MSA underwent [123I]Ioflupane SPECT and [123I]MIBG scintigraphy. In each of these techniques, qualitative assessment was compared with quantitative assessment. Results: SPECT visual assessment was positive in 93.5% of subjects (S = 95.24%; PPV = 93.02%). A cut-off of 1.363 was established for overall S/O index (S = 85.7%, E = 100%). Visual assessment of scintigraphy was positive in 73.1% (S = 78.57%, PPV = 94.29%). For the delayed heart/medistinum ratio (HMR) a cut-off of 1.43 (S = 85.3, E = 100%) was obtained. For each unit increase in delayed HMR, the suspicion of MSA increased by 1.58 (OR = 1.58, p < 0.05). The quantitative assessment showed an association with the visual assessment for each technique (p < 0.05). Conclusions: Both tests are useful in MSA diagnosis. Comparatively, we did not observe a clear superiority of either. Striatal and myocardial deterioration do not evolve in parallel. Qualitative assessment is crucial in both techniques, together with the support of quantitative analysis. Delayed HMR shows a direct relationship with the risk of MSA.